1975
DOI: 10.1116/1.568687
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the initial nucleation of alumina on cemented-carbide substrates in the CVD process

Abstract: Alumina nuclei were deposited, using chemical vapor deposition (CVD), under varying process conditions on polished cemented-carbide substrates (WC+TiC, TaC, NbC+Co) for 60 s in order to study the nucleation stage. During the heating up of the substrates the binder of the polished surfaces diffused onto the carbide surfaces. The surface of the WC was thereby converted to η-phase, while no attack on the (Ti,W)C surfaces could be detected. After the short deposition the alumina nuclei were counted. The nucleation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

1978
1978
1992
1992

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…Whilst the supersaturation of the AI-donor (AlCI 3 ) decreases as the deposition temperature increases, that of the O-donor (H 2 0 vapour from CO 2 and H 2 ) increases because the H 2 0 inlet concentration is more sensitive to temperature than the H 2 0 equilibrium concentration, the resulting exponentially increased growth rate accounting for the coarser grains found to exist at the higher deposition temperatures. It is pertinent to point out that whilst Park et al refer to an increase in the supersaturation of O-donor with increasing deposition temperature (in agreement with the findings of 10hannesson and Lindstrom [41]) this is in direct contrast to the findings of Lindstrom and 10hannesson [29] and Kim et al [43], according to whom the supersaturation of O-donors decreases with increasing deposition temperature. In their work Colmet and Naslain [27] observed that AlP3 coatings deposited at a deposition temperature of 1173 K (900°C) and a total pressure of 0.8 atm, with the other deposition conditions as specified earlier in Section 2.1, were composed of nodules whilst coatings deposited at a temperature of 1323 K (10S0°C) exhibited "well-shaped", pyramidal AIP3 crystals.…”
Section: Effect Of Deposition Temperaturecontrasting
confidence: 56%
See 3 more Smart Citations
“…Whilst the supersaturation of the AI-donor (AlCI 3 ) decreases as the deposition temperature increases, that of the O-donor (H 2 0 vapour from CO 2 and H 2 ) increases because the H 2 0 inlet concentration is more sensitive to temperature than the H 2 0 equilibrium concentration, the resulting exponentially increased growth rate accounting for the coarser grains found to exist at the higher deposition temperatures. It is pertinent to point out that whilst Park et al refer to an increase in the supersaturation of O-donor with increasing deposition temperature (in agreement with the findings of 10hannesson and Lindstrom [41]) this is in direct contrast to the findings of Lindstrom and 10hannesson [29] and Kim et al [43], according to whom the supersaturation of O-donors decreases with increasing deposition temperature. In their work Colmet and Naslain [27] observed that AlP3 coatings deposited at a deposition temperature of 1173 K (900°C) and a total pressure of 0.8 atm, with the other deposition conditions as specified earlier in Section 2.1, were composed of nodules whilst coatings deposited at a temperature of 1323 K (10S0°C) exhibited "well-shaped", pyramidal AIP3 crystals.…”
Section: Effect Of Deposition Temperaturecontrasting
confidence: 56%
“…In a similar investigation, 10hannesson and Lindstrom [41] 3 ) the measured saturation density of AlP3 clusters was found to be 3 x 10' cm· 2 • According to Kornmann et ai, from work carried out at different deposition temperatures with different reactant gas compositions to those previously quoted, the saturation density of Al 2 0 3 nuclei also increases with increasing AlCI 3 supersaturation.…”
Section: Effect Of Deposition Temperaturementioning
confidence: 80%
See 2 more Smart Citations
“…Since then, this new porous material has been investigated particularly because of its potential use in integrated circuit technology(3)(4)(5)(6). Since then, this new porous material has been investigated particularly because of its potential use in integrated circuit technology(3)(4)(5)(6).…”
mentioning
confidence: 99%